Impact of Biopsychosocial Factors on Chronic Pain in Persons With Myotonic and Facioscapulohumeral Muscular Dystrophy - Miró, Jordi (2009)
To assess the role of biopsychosocial factors in patients with type 1 myotonic and facioscapulohumeral muscular dystrophy (MMD1/FSHD) with chronic pain. Associations between psychosocial factors were found to be important in other samples of persons with pain and both psychological functioning and pain interference in a sample of patients suffering from MMD/FSHD. Prospective, multiple group, survey study of 182 patients with confirmed MMD1 and FSHD. Participants completed surveys assessing pain interference and psychological functioning, as well as psychosocial, demographic, and injury-related variables. Analyses indicated that greater catastrophizing was associated with increased pain interference and poorer psychological functioning, pain attitudes were significantly related to both pain interference and psychological functioning, and coping responses were significantly related only to pain interference. In addition, greater perceived social support was associated with better psychological functioning. The results support the use of studying pain in persons with MMD/FSHD from a biopsychosocial perspective, and the importance of identifying psychosocial factors that may play a role in the adjustment to and response to pain secondary to MMD/FSHD.